An unexpected discovery: Johann Heinrich von Thuenen and the tragedy of the commons - Ludwig Nellinger (Universität Rostock, Institut für Volkswirtschaftslehre, 2014)
William Forster Lloyd's 1833 sketch about poor cattle on the commons and the well-fed animals on the adjacent enclosures published in his 'Two lectures on the checks to population' has hitherto been assessed as one starting point of the economics of renewable resources. In the 20th century the question of the use of common property resources has initially been treated by fisheries economists, at first in unknown publications of Jens Warming in 1911 and 1931, and after a disruption of more than 40 years starting again with the contributions of Gordon and Scott in the 1950s. Important results have been the derivation and presentation of the economic criteria for the open access equilibrium case on the one hand and the private property equilibrium case on the other hand. Garrett Hardin's well known 1968 Sciences article brought a new title and increased awareness to the 'tragedy of the commons' and Elenor Ostrom's 2009 nobel prize in economics finally underlined the importance as well as the diversity of institutional rules to achieve an efficient use of the natural resources - challenging the favored liberal concept of a privatization of scarce resources. Johann Heinrich von Thuenen's contributions on the commons - hidden in an 1831 article about urban agriculture in the journal 'Neue Annalen der Mecklenburgischen Landwirtschaftsgesellschaft' and in an unpublished manuscript - have been totally neglected until now, although he published his article about the core problem of the commons two years earlier than William Forster Lloyd and almost in the clarity of the fisheries economists 80 resp. 120 years later. He not only presented the correct allocation criteria for both property rights scenarios but additionally developed a framework a) how to gain the maximal rent of a resource through an auction system - drafting the first demand table b) how to redistribute the gains to the communal property owners - developing an adequate compensation mechanism c) and finally how to establish this institutional innovation democratically - thereby applying important elements of Elenor Ostrom's Common Property Rights Framework. Due to these contributions Johann Heinrich von Thuenen deserves the title of the founder of the economics of renewable resources. Moreover, in combination with his publications on forestry, land use, soil improvement and agricultural processing industries he should also be seen as the creator of a discipline which got its name but now, the creator of bioeconomics.
Keywords: B13; B15; B16; Q15; Q21; Q22; Q24; 330; bioeconomics; economics of renewable resources; tragedy of commons; fisheries economics; urban agriculture; factor demand table; auction system